Reviews September 2018. Issue 1 (1st October 2018) - Seelow, Atli Magnus; Andersen, Angela; Van Gerrewey, Christophe; Popescu, Carmen
Abstract : Seelow, AM. Review of: Magnus Brechtken, Albert Speer. Eine deutsche Karriere, Munich: Siedler Verlag, 2017. Andersen, A. Review of: ΣΕΠΤΕΜΒΡΙΑΝA/September 55, Keller Gallery, Cambridge, MA, 2016; !f Istanbul Independent Film Festival, Istanbul, 2017. Van Gerrewey, C. Review of: Stedelijk Base, Stedelijk Museum Amsterdam, Amsterdam, 2017. Popescu, C. Review of: Shrinking Cities in Romania, National Museum of Contemporary Art, Bucharest, 2016.